Postharvest Application of Novel Bio-Based Antifungal Composite Edible Coatings to Reduce Sour Rot and Quality Losses of ‘Valencia’ Oranges - Álvarez, María Victoria; Pérez-Gago, María B.; Taberner, Verònica; Settier-Ramírez, Laura; Martínez-Blay, Victoria; Palou, Lluís (MDPI, 2023)
Sour rot, caused by Geotrichum citri-aurantii, can produce significant postharvest losses of citrus fruits and, currently, cannot be effectively controlled by the postharvest fungicides registered in EU countries. Therefore, novel antifungal edible coatings (ECs) based on citrus pectin and beeswax and enriched with eugenol (EG), geraniol (GR), propolis extract (PR) or essential oils (EOs) from Satureja montana (SA), Cinnamomum zeylanicum (CI), or Commiphora myrrha (CM), were developed as alternatives to reduce sour rot and preserve the postharvest quality of ‘Valencia’ oranges. These natural agents were incorporated into the EC formulation and then applied to inoculated oranges. ECs enriched with EG (2–8 g/kg), GR (4 and 8 g/kg), PR (5–20 g/kg), and CM EO (15 g/kg) reduced disease incidence and severity by 75 to 100% compared to uncoated oranges after 20 days of incubation at 20 °C. ECs containing EG (8 g/kg), GR (4 g/kg), and PR (20 g/kg) reduced weight loss and retained firmness of oranges after 14 days of shelf life at 20 °C. Furthermore, all tested ECs maintained the fruit’s sensory and physicochemical quality. Overall, the EG-enriched pectin EC performed best, showing potential as a safe, bio-based alternative to conventional waxes containing synthetic fungicides for the management of citrus postharvest sour rot.